Perspectives on Antiphonal Calling, Duetting and Counter-Singing in Non-primate Mammals: An Overview With Notes on the Coordinated Vocalizations of Bamboo Rats (Dactylomys spp., Rodentia: Echimyidae) - Vanderhoff, E. Natasha; Bernal Hoverud, N. (Frontiers in Ecology and Evolution, 2022)
Temporally coordinated interactive vocalizations are important means of communication between individuals in various animal taxa. In mammals, interactive calling and singing can be highly synchronized to create either overlapping or antiphonal duets while in others, competitors antagonistically vocalize, engaging in counter-singing. Among non-primate mammals these vocalizations are considered rare and poorly understood. We provide an overview of antiphonal calling, duetting and counter-singing in non-primate mammals. Many of these coordinated vocalizations play a role in social interactions and allow mammals to convey information to other members of the social unit in visually inaccessible environments. South American Bamboo rats Dactylomys spp. are arboreal bamboo specialists found in dense bamboo thickets in Bolivia, Peru, Ecuador, Brazil and Colombia. These nocturnal rodents are rarely seen but can be easily heard because of their loud and distinctive staccato vocalizations. We provide some evidence that Bamboo rats engage in duetting, and as such they provide another case of a mammalian species, in which to investigate temporally coordinated interactive singing. We urge researchers to work towards common definitions of temporally coordinated vocalizations and to search for more mammals that utilize such vocalizations.